Animal experiment on osseointegration of porous titanium root analogue implants with composite CSn-TAK242 coating - Li, Hui; Luo, Dan; Gao, Yudong; Wang, Dashan; Yang, Jianjun; Xu, Zexian (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveChitosan nanoparticles loaded with TLR4 inhibitors (TAK242) were coated on porous titanium root analogue implants and placeded into beagles to investigate the role of TLR4 inhibitors in inhibiting inflammatory reactions and promoting osseointegration in vivo.MethodsThe control group consisted of porous titanium root analogue implants fabricated via digital medical technology and 3D printing, while the experimental group included porous titanium root analogue implants with CSn and CSn-TAK242 bioactive coatings. Three groups of implants were inserted into the jaws of dogs, with their stability coefficients immediately measured upon implantation. After 3 months, samples were collected, and the bone integration and gingival attachment of the three groups were assessed using X-rays, Micro-CT, and histological section staining.ResultsAll groups of porous titanium root analogue implants were correctly placed within the alveolar sockets. The stability coefficients of the implants immediately post-implantation in the control group, CSn group, and CSn-TAK242 group were (64.29 ± 4.01), (62.55 ± 1.98), and (64.59 ± 3.28), respectively, with no significant statistical difference (P>0.05). Three months post-surgery, imaging and histological examinations revealed bone integration with the surrounding bone tissue for all implant groups. BIC results showed: control group (68.11 ± 3.63)%, CSn group (71.07 ± 2.83)%, and Csn-TAK242 group (78.6 ± 4.52)%, with the BIC being highest in the CSn-TAK242 group, followed by the CSn group, and lowest in the control group (P<0.05). More importantly, compared with the control group, the BV/TV of the CSn-TAK242 group was significantly higher. In addition, the Tb.Th of the CSn-TAK242 group was significantly higher than that of the control group and CSn group (P<0.05). The smooth structures at the upper ends of the implants had tight gingival tissue attachment.ConclusionPorous titanium root analogue implants consistent with the target root morphology were successfully fabricated using digital medical technology and 3D printing. The composite CSn-TAK242 coating further enhanced the osseointegration effects of these implants.